Pengaruh Lama Waktu Microwave Assisted Extraction (MAE) Terhadap Rendemen Gelatin Dari Ceker Ayam - Kholis, Muhammad Nur; Mufandi, Ilham; Pratama, Yogi (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Gelatin is a collagen-derived product widely used in the food, pharmaceutical, and cosmetic industries. The extraction of gelatin from chicken bones requires efficient methods to increase yield and reduce energy consumption. One of the effective methods is Microwave-Assisted Extraction (MAE). This study aims to evaluate the effect of extraction time on gelatin yield and calculate the mass balance in the extraction process by MAE method. The research was conducted with variations in extraction time of 2, 3, and 4 hours. The results showed that the gelatin yield at extraction times of 2, 3, and 4 hours were 8.5%, 10.2%, and 12.1%, respectively. ANOVA test with a significance level of 0.05 showed a significant difference (p < 0.05), indicating that extraction time affects the yield. Mass balance was calculated to evaluate the efficiency and mass distribution at each extraction stage. The results showed that longer extraction time increased the yield, with 4 hours yielding the highest yield. This study concludes that MAE increases gelatin yield, but needs further optimization in terms of time and energy efficiency.